Operational Amplifier Circuits - Nelson, J. (Newnes, 2013)
This book, a revised and updated version of the author's Basic Operational Amplifiers (Butterworths 1986), enables the non-specialist to make effective use of readily available integrated circuit operational amplifiers for a range of applications, including instrumentation, signal generation and processing. It is assumed the reader has a background in the basic techniques of circuit analysis, particularly the use of j notation for reactive circuits, with a corresponding level of mathematical ability. The underlying theory is explained with sufficient but not excessive, detail. A range of computer programs provides assistance with the required calculations. The widespread availability of operational amplifiers in the form of low-cost integrated circuits means that today a modular approach to analog circuit design is possible. In many cases, a single operational amplifier in conjunction with a small number of passive components may be all that is required for a particular function.